The Influence of Cognitive Approach in Reducing Stress in Self-Adjustment of Out-of-Town University Students - Salsabila Nur Kamilah; Mariska Juliana; Karima Alya; Halim Purnomo (CV. Doki Course and Training, 2024)
This study explores the role of the cognitive approach in reducing stress among out-of-town students at the Faculty of Science and Technology. Students who come from different cities or countries often face challenges in adapting to a new environment and coping with high academic demands. The cognitive approach is used as a potential strategy to help them manage adjustment stress.The study adopts a pure experimental design with a randomized pretest-posttest control group design and follow-up. The results indicate a significant change in the level of adjustment stress in the experimental group compared to the control group.Subjects who showed the most noticeable decrease in stress at the posttest stage were subject 4, while subject 3 experienced a smaller decrease. However, during the follow-up stage, subject 3 showed a remarkable change.This research shows that the cognitive approach with the three-column technique can effectively reduce adjustment stress among out-of-town students. These findings can provide guidance for higher education institutions in developing more effective programs to help students cope with adjustment stress.